A METÁFORA E A CONSTITUIÇÃO DA SUBJETIVIDADE NA PSICOSE - Schäffer, Margaret; Teixeira, Marlene; Flores, Valdir do Nascimento (Organon, 2002)
This paper aims to reflect on the role and relevance of metaphorin the psychotic discourse. In this way, activity verbal can be definedas a place of the manifestation of the subjective in the language. As aconsequence, metaphor is not describe as a closed structure, but it is to becaptured in the very process of the enunciation.